2008
DOI: 10.1063/1.3007988
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the shear-mechanical and dielectric relaxation processes in two monoalcohols close to the glass transition

Abstract: Shear-mechanical and dielectric measurements on the two monohydroxy (monoalcohol) molecular glass formers 2-ethyl-1-hexanol and 2-butanol close to the glass-transition temperature are presented. The shear-mechanical data are obtained using the piezoelectric shear-modulus gauge method covering frequencies from 1 mHz to 10 kHz. The shear-mechanical relaxation spectra show two processes, which follow the typical scenario of a structural (alpha) relaxation and an additional (Johari-Goldstein) beta relaxation. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
86
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(99 citation statements)
references
References 41 publications
9
86
1
3
Order By: Relevance
“…There is also a smaller, and broader, peak at higher frequencies, which is to be identified as the ␣-relaxation. 7,9 We also show the spectra obtained at the same temperature using a thin ͑5 m͒ Teflon sheet covering the upper electrode. We see that, apart from a general reduction of the response, contributions from dc conductivity are reduced without significantly affecting the rest of the spectrum.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also a smaller, and broader, peak at higher frequencies, which is to be identified as the ␣-relaxation. 7,9 We also show the spectra obtained at the same temperature using a thin ͑5 m͒ Teflon sheet covering the upper electrode. We see that, apart from a general reduction of the response, contributions from dc conductivity are reduced without significantly affecting the rest of the spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…This further explains why the Debye-like process is not readily observable in other techniques such as e.g., mechanical spectroscopy. 9 The shape of the Debye-like peak in the polyalcohols is well described with a Cole-Cole function ͓Eq. ͑3͒ with ␤ =1͔ with only a slight symmetric broadening, partly because of the Teflon film ͑as discussed above͒.…”
Section: -3mentioning
confidence: 99%
“…24 One of the monohydroxyl alcohols 2-ethyl-1-hexanol has been studied extensively in the literature mainly with a view to resolving as to which of the two processes I or II, is responsible for the structural relaxation. [18][19][20][29][30][31] In particular, dielectric features have been compared with the observations made from calorimetry, 29 mechanical spectroscopy, 29 and recently NMR. 31 The effects of high pressure on dielectric properties have been investigated by three groups.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] This is a slow mode which is often very intense in the dielectric signal sometimes completely covering the signal of the α-relaxation. 12,[14][15][16][17] Experimental observations have revealed that this mode has an exponential character, hence the name Debye relaxation. The prominent dielectric amplitude of the Debye relaxation in monohydroxy alcohols cannot be explained exclusively from the molecular dipole moment, but it is due to hydrogen bonding associations (chains, rings, or other units) that induce changes in the orientational correlations of dipoles.…”
mentioning
confidence: 99%